2017
DOI: 10.1097/md.0000000000005786
|View full text |Cite|
|
Sign up to set email alerts
|

Hypertonic saline protects brain endothelial cells against hypoxia correlated to the levels of estimated glomerular filtration rate and interleukin-1β

Abstract: Objective:The aim of this study was to verify the protective effect of hypertonic saline (HS) on brain endothelial cells under hypoxic conditions and the relevant underlying mechanism.Methods:bEnd.3 cells were treated with oxygen-glucose deprivation (OGD)-induced injury. To measure HS performance, cell viability was determined using the 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium salt assay, and cell apoptosis was assessed by flow cytometry and Terminal deoxynucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In bEnd.3 cells, Liu and colleagues found a time-dependent increase in the levels of cleaved caspases-3 and -9 between 6 and 12 hours of OGD [91]. Other studies corroborate these findings of apoptotic cell death in bEnd.3 cells [9296], in a human brain microvascular EC line (HBMEC [9799]) as well as in primary brain microvascular ECs from rats [100, 101] and mice [75, 102104].…”
Section: Systematic Review Of Ec Death In Strokementioning
confidence: 84%
“…In bEnd.3 cells, Liu and colleagues found a time-dependent increase in the levels of cleaved caspases-3 and -9 between 6 and 12 hours of OGD [91]. Other studies corroborate these findings of apoptotic cell death in bEnd.3 cells [9296], in a human brain microvascular EC line (HBMEC [9799]) as well as in primary brain microvascular ECs from rats [100, 101] and mice [75, 102104].…”
Section: Systematic Review Of Ec Death In Strokementioning
confidence: 84%
“…Although it is not completely understood whether all of these BMEC-derived soluble factors induced by IL-1β disrupt the barrier integrity of BMECs, these factors may participate in the destructive effect of IL-1β on the BBB in an autocrine manner. Importantly, the ability of BMECs to secrete IL-1β in response to oxygen glucose deprivation and TNF-α should also be considered in IL-1β-induced BBB dysfunction ( Matsumoto et al, 2014 ; Chen et al, 2017 ).…”
Section: Inflammatory Mediators Involved In Bbb Dysfunction and Related Intracellular Signaling Pathways In Bmecsmentioning
confidence: 99%
“… Flow cytometry, RNA-seq, Quantitative real-time polymerase chain reaction, western blot, enzyme-linked immunosorbent assay How do the levels of IL-1β and EGFR is correlated to the performance of HTS and apoptosis? 41 Hypertonic saline (HTS) HeLa cells Increasing NaCl concentration more than 130 mM decreases growth rate, increases protein levels, and cell volume. Biochemical analysis, hemocytometry, microscopy Ionic and osmotic effects of HTS in the metabolism of HeLa cells 50 Hypertonic sucrose (HTSu) Human leukemia cells(U937) U937 cells developed apoptosis thanks to regulatory volume increase in HTSu.…”
Section: Resultsmentioning
confidence: 99%
“…Most IVF investigations have focused on revealing their influence on medication stability, compatibility and administration 18 . To date, there have been few quantitative in vitro studies about the influence of IVF on cellular level, which are mostly reported for blood cells and endothelial cells 18,40,41 .…”
Section: Discussionmentioning
confidence: 99%